"Predelujem stare mojstre, k so jim že potekle avtorske pravice." - Smolej, Tone (Vestnik za tuje jezike, 2015)
The paper examines Andrej Rozman's creative reception of Jean-Baptiste Poquelin Moliere's comedies The Miser and The Imaginary Invalid. The Miser, which had been translated into Slovenian a number of times, was recast in 2007 by the Slovenian comedy writer as a comic one-man play featuring Harpagon as an entrepreneur, who discusses many topical Slovenian problems in front of the audience, with occasional allusions to his son and daughter, whom he wants to marry off according to his economic interests. In this modern version, everything is explained and solved by the daughter's phone call. In 2011, The Imaginary Invalid inspired another of Rozman's plays, Hiphophondrija, which features the family father as a chatty tycoon. Closest to the original is the scene with the young doctor. Both texts are travesties, rendering Moliere's plots in a lower register and setting them in contemporary Slovenia. On the other hand, certain scenes which come closest to Moliere are couched in "precious" idiom.
Keywords: Moliere, 1622-1673; "L'avare"; "Le malade imaginaire"; Rozman, Andrej, 1955-; "Skopuh"; "Hiphophondrija"; francoska književnost; French literature; Slovene literature; slovenska književnost; primerjalna književnost; comparative literature; literarna recepcija; komedije; komične monodrame; travestije; primerjalne študije